Legal Protection of Personal Data as Privacy Rights of E-Commerce Consumers Amid the Covid-19 Pandemic - Haganta, Raphael (Lex Scientia Law Review, 2020)
The use of e-commerce in the midst of the COVID-19 pandemic shows an increase. This is due to the publication of several regulations that limit everyone's activities outside the home, affecting conventional trading activities online by utilizing e-commerce. Although providing benefits during the pandemic, e-commerce has a vulnerability to personal data protection. Through this paper, the authors use normative legal research methods, intending to know the concept of personal data as a right of privacy and the construction of Indonesia's positive laws in legal protection of the personal data of e-commerce consumers.The use of e-commerce in the midst of the COVID-19 pandemic shows an increase. This is due to the publication of several regulations that limit everyone's activities outside the home, affecting conventional trading activities online by utilizing e-commerce. Although providing benefits during the pandemic, e-commerce has a vulnerability to personal data protection. Through this paper, the authors use normative legal research methods, intending to know the concept of personal data as a right of privacy and the construction of Indonesia's positive laws in legal protection of the personal data of e-commerce consumers.